Assessment Of The Effect Of Radionuclides From Malaysian Soils On Environmental Safety - Hj.Ismail, Marzuki (1997)

(untitled)
Natural radioactive sources are the major contributor to human radiation exposure. The accumulation of radioactivity in surface soil is of concern since growing vegetation will take up radionuclides through roots and incorporate them into variou parts of the plants. Study of the level of radioactivity is soil is also important because natural exposure represents a reference against which exposure to man-made sources may be compared. not only for standards-setting purposes. but also in epidemiological studies. However little information is available on the distribution of natural radionuclides in Malaysian surface soil.